MINAT MASYARAKAT TERHADAP MODEL PENDIDIKAN MADRASAH DI MAGELANG DAN DEMAK - Aji Sofanudin (Badan Litbang dan Diklat Kementerian Agama RI, 2012)
AbstractThis study aims to determine how the model of the enlargement of public interest in Islamic school (madrasah) is. This study used the Research and Development method. Sources of data were parents of students and administrators of Islamic Elementary School (MI) and Islamic Junior High School (MTs) in Central Java. The findings show that highly demanded madrasah model is madrasah which having a concern with the community assessment aspect and the madrasah management. The enlargement of public interest model in madrasah is done through the following efforts (1) Formation of Madrasah Positive Image, (2) Madrasah Achievement; Academic and Non-academic, (3) Intensification and ExÂtensification of Madrasah Publication, (4) Featured Program oriented to the community needs, ( 5) Compliance with National Education Standard, (6) Attractive Appearance of Madrasah. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana model peningkatan minat masyarakat terhadap madrasah. Penelitian ini menggunakan Research and Development. Sumber datanya adalah orang tua siswa dan pengelola Madrasah Ibtidaiyah dan Tsanawiyah di Jawa Tengah. Hasilnya, model madrasah yang diminati masyarakat adalah madrasah yang memperhatikan aspek penilaian masyaÂrakat dan pengelolaan madrasah. Model peningkatan minat masyarakat terhadap madrasah melalui upaya sebagai berikut (1) Pembentukan Citra Positif Madrasah, (2) Peningkatan Prestasi Madrasah; Akademik dan Non akademik, (3) Intensifikasi dan ekstensifikasi Publikasi Madrasah, (4) Program Unggulan yang Berorientasi Kebutuhan Masyarakat, (5) Pemenuhan Standar Nasional Pendidikan, (6) Penampilan Madrasah yang Menarik.